Discontinuity in the history of taphonomy: rediscovery of early works during the second half of the twentieth century - André Silva; Hermínio Ismael de Araújo Júnior; Rodolfo Dino (Filosofia e História da Biologia)
This paper aims to elucidate factors that contributed to the temporary loss of the European tradition of Taphonomy, developed during the first half of the twentieth century, and its rediscovery and reinvention in North America during the Post-War. Such factors are not restricted to the intellectual content of papers and books produced by researchers but have to do also with linguistic, cultural, historical, and institutional matters, which have shaped and conditioned the reception of ideas and concepts within Paleontology during the twentieth century. These factors include the transition from a multilingual scientific culture to a monolingual one, the shift of palaeontology’s centre from Europe to the United States, and the ideology of researchers, among other factors.